2023
DOI: 10.3390/ma16020693
|View full text |Cite
|
Sign up to set email alerts
|

Eco-Friendly Polysaccharide-Based Synthesis of Nanostructured MgO: Application in the Removal of Cu2+ in Wastewater

Abstract: The present study described three synthesis routes using different natural polysaccharides as low-cost non-toxic fuels and complexing agents for obtaining MgO. Cassava starch, Aloe vera leaves (mainly acemannan) gel, and citric pectin powder were mixed with magnesium nitrate salt and calcined at 750 °C for 2 h. The samples were named according to the polysaccharide: cassava starch (MgO-St), citrus pectin (MgO-CP), and Aloe vera (MgO-Av). X-ray diffraction identified the formation of a monophasic periclase stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…The values obtained for chromium removal can be compared to studies reported in the literature with materials typically used for Cr 3+ and Cr 6+ removal, as shown in Table 6. In addition, the adsorption capacity of Cr 3+ by MgO can be highlighted by the ion exchange process that occurs when MgO is added to different concentrations of Cr 3+ ion solutions [14]. In Cr(VI) removal studies by Alvares et al [31], zeolites were used in a discontinuous system for tannery effluent, opting for 0.0057 mg/g in the removal tests, with considerably low values.…”
Section: Chemical Composition By Icp-oesmentioning
confidence: 99%
See 2 more Smart Citations
“…The values obtained for chromium removal can be compared to studies reported in the literature with materials typically used for Cr 3+ and Cr 6+ removal, as shown in Table 6. In addition, the adsorption capacity of Cr 3+ by MgO can be highlighted by the ion exchange process that occurs when MgO is added to different concentrations of Cr 3+ ion solutions [14]. In Cr(VI) removal studies by Alvares et al [31], zeolites were used in a discontinuous system for tannery effluent, opting for 0.0057 mg/g in the removal tests, with considerably low values.…”
Section: Chemical Composition By Icp-oesmentioning
confidence: 99%
“…According to Balaba et al [14], the metal removal mechanism by MgO involves at least three steps, shown in Equations ( 3)-( 5).…”
Section: Chemical Composition By Icp-oesmentioning
confidence: 99%
See 1 more Smart Citation